Longhouses, Schoolrooms, and Workers’ Cottages: Nineteenth-Century Protestant Missions to the Tsimshian and the Transformation of Class Through Religion - Neylan, Susan (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2000)
AbstractThis paper explores the blurring of boundaries among class identities in nineteenth-century Protestant missions to the Tsimshian, Aboriginal people of the northwest British Columbia coast. Through an exploration of the nature of Christian chiefs, Tsimshian demand for literacy and schooling, and finally mission housing, this paper highlights ways in which the class implications of religious association had profoundly different meanings in Native and non-Native milieus. Scholars must take into account historical Aboriginal perspectives not only on conversion, but on their class positions in mission Christianity and more precisely, how their roles within the mission sphere were informed by their own notions of class. While some Native converts undoubtedly utilized conversion to Christianity to circumvent usual social conventions surrounding rank, privilege, and access to spiritual power, other Tsimshian sought transformation by using these new forms of spirituality to bolster their existing social positions.